Low‐Dimensional Metal‐Halide Perovskites as High‐Performance Materials for Memory Applications - Guan, Xinwei; Lei, Zhihao; Yu, Xuechao; Lin, Chun‐Ho; Huang, Jing‐Kai; Huang, Chien‐Yu; Hu, Long; Li, Feng; Vinu, Ajayan; Yi, Jiabao; Wu, Tom (Small (Weinheim an der Bergstrasse, Germany), 2022)
Metal‐halide perovskites have drawn profuse attention during the past decade, owing to their excellent electrical and optical properties, facile synthesis, efficient energy conversion, and so on. Meanwhile, the development of information storage technologies and digital communications has fueled the demand for novel semiconductor materials. Low‐dimensional perovskites have offered a new force to propel the developments of the memory field due to the excellent physical and electrical properties associated with the reduced dimensionality. In this review, the mechanisms, properties, as well as stability and performance of low‐dimensional perovskite memories, involving both molecular‐level perovskites and structure‐level nanostructures, are comprehensively reviewed. The property–performance correlation is discussed in‐depth, aiming to present effective strategies for designing memory devices based on this new class of high‐performance materials. Finally, the existing challenges and future opportunities are presented. Low‐dimensional halide perovskites are among the most rapidly emerging building blocks for optoelectronic applications. This review elucidates the advantages and the crucial role of molecular‐/structure‐level low‐dimensional halide perovskites in achieving high performance and enhanced stability in memory applications.